INFLUENCE OF INNOVATIVE SHRM PRACTICES ON EFFECTIVENESS OF AUTOMOBILE FIRMS IN CHENNAI - LATHA, R.; JAGADEESAN, P. (International Journal of Psychosocial Rehabilitation, 2020)
Human Resource Management (HRM) has been developed into Strategic Human Resource Management (SHRM) by researchers who seek to emphasise the need to ensure the effective functioning of an organisation. To this end, many researchers have established that innovative Strategic HRM practices would lead to an improvement in organisational performance and effectiveness. When organisations believe in implementing innovative strategic HRM practices it is sure to replace the traditional and looked down HR policies and procedure with one that help HR mangers in linking the HR objectives and strategy with the overall goals of the organisation. This article throws light on the influence of innovative SHRM practice on the effectiveness of automobile firms in Chennai.